PENENTUAN PRODUK UNGGULAN DAERAH MENGGUNAKAN KOMBINASI METODE AHP DAN TOPSIS (Studi Kasus Kabupaten Rembang) - A AVIV MAHMUDI; MUHAMMAD TAHWIN (Universitas PGRI Semarang, 2016)
UKMM in Rembang district has a lot of potential of hearts produce seed products, but theproducts were identified Operates yet clear The Become Top Priority as ungulan products. It causes lessfocus Singer Development and Language Development Of County Government hearts competitivenessenhancement Products generated. The methods used determine hearts hearts Singer Research Products ofRegions is Analytical Hierarchy Process (AHP) The combined WITH Methods Techniques For OtherReferences by Similarity to Ideal Solution (TOPSIS). AHP is used to determine the weight of the reviewsof 6 Criteria That turnover, labor, Term Company, target market, Daniel Raw Materials ProductionPeriod. While alternative perangkingan Products From SMEs using TOPSIS Method. Respondentsdetermined TECHNIQUE purposive sampling, selected based on the criteria of expertise and involvementhearts SME development activities. From the findings of Data Processing The resulting weights of eachcriterion Massing turnover is 35%, Labour 17%, 14% Raw materials, Term Production 14%, the targetmarket is 13% and 8% Term of the Company. The results of the analysis and data processing TIN ValuePreference From EVERY alternative, as the Fish Processing Products of Rembang WITH PreferencesValue 0.8310, Ship BY Value Preferences 0.7221, Batik WITH preference value 0.6767, and then the saltMaking wooden furniture, embroidery And the latter in is Making tempeh.